Peningkatan Hasil Belajar Seni Budaya Menggunakan Metode Demonstrasi Siswa Kelas IV SDN 176 Tanabatue Kabupaten Bone - Awaluddin Muin; Muhammad Awal Nur; Nurnilan Sari Saputri (Indonesian Journal on Education (IJoEd), 2025)
This study was motivated by the low learning outcomes of fourth-grade students in the Cultural Arts subject at SDN 176 Tanabatue, Bone Regency. The objective of this research was to improve student achievement through the implementation of the demonstration method. The study employed a Classroom Action Research (CAR) approach conducted over two cycles, involving 21 students as participants. Data were collected using documentation, achievement tests, and student activity observations. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicated a significant improvement in student learning outcomes following the application of the demonstration method. The percentage of students achieving mastery increased from 66.66% in the first cycle to 81% in the second cycle. These findings suggest that the demonstration method enhances students' conceptual understanding and practical skills in Cultural Arts learning. Therefore, it can be concluded that the demonstration method is an effective instructional strategy for improving student learning outcomes at the elementary school level.